Penerapan Permainan dalam Meningkatkan Gerak Lokomotor pada Siswa Kelas VI SD Negeri 4 Bubutan Surabaya - Dimas Danny Yudatama; Advendi Kristiyandaru; Rinda Kuswati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to improve the locomotor movement ability in grade VI SDN Bubutan 4 Surabaya with the application of games, The problem is that students in grade VI B still have difficulties in locomotive movement, In cycle 1 using the application of games such as relay games and jumping rope, data is collected through direct observation and assessment of student skills before and after the implementation of the activity, analysis shows that some students still do not show significant improvement in locomotor movement ability, In cycle 2 the game is simplified. The results of the analysis showed that the improvement of locomotor movement ability became more consistent across all groups of students. The conclusion of this study is that the application of the game method is effective in improving locomotor movement skills in grade VI B SDN Bubutan 4 Surabaya. Classroom action research (PTK) with Cycle I and Cycle II. The subject of this study is 32 students of class VI B SD Negeri 4 Bubutan, the application of the game aims to improve the locomotor motion of students in class VI B SD Negeri 4 Bubutan. From the results of the Implementation of Cycle I, students in class VI B reached a percentage of 43% and the Implementation of Cycle II reached a percentage of 87%, with this the application of the game method in improving the locomotor movement of students in class VI B has reached a classical value with a provision of 85%.